Solvent-free Hot Melt Extrusion Technique in Improving Mesalamine Release for Better Management of Inflammatory Bowel Disease - Sahoo, Rudra Narayan; De, Ananya; Kataria, Vishal; Mallick, Subrata (Indian Journal of Pharmaceutical Education and Research, 2019)
Background: Poor oral bioavailability of mesalamine (Mes) is due to extensive metabolism in the intestinal epithelial cells in addition to the liver. Purpose: Improved mesalamine release by Hot-Melt Extrusion (HME) technique could be utilized for better management of Inflammatory Bowel Disease (IBD). Methods: Mes and hydrophilic polymers like EudragitEPO, KollidonVA-64 and PEG 6000 were hot-melt extruded using a co-rotating twin-screw laboratory extruder. Results: The minor shifting with significantly reduced intensity and disappearance of peak in the Differential Scanning Calorimetry (DSC) thermogram could be attributed to some solid–solid interaction and not necessarily any incompatibility. Fourier-Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM) confirmed the transformation of individual drug crystal into accumulations of small crystallites due to partial or almost complete amorphization. Continuous manufacturing of stable amorphous solid dispersion by solvent-free drug loading Hot-melt extrusion technique has been found feasible in improving drug release compared to mesalamine alone in simulated gastric fluid (f1= 0.3 to 11.1 and f2 = 26 to 49). Conclusion: Melt dispersion samples have exhibited significantly improved mesalamine release and could be utilized for better management of Inflammatory Bowel Disease (IBD).
Keywords: Hot-melt extrusion; Solvent-free drug loading; Mesalamine; Feret diameter; Improving Release